Enhanced Positive Emotional Reactivity Undermines Empathy in Behavioral Variant Frontotemporal Dementia - Hua, Alice Y.; Sible, Isabel J.; Perry, David C.; Rankin, Katherine P.; Kramer, Joel H.; Miller, Bruce L.; Rosen, Howard J.; Sturm, Virginia E. (Frontiers in Neurology, 2018)
Behavioral variant frontotemporal dementia (bvFTD) is a neurodegenerative disease characterized by profound changes in emotions and empathy. Although most patients with bvFTD become less sensitive to negative emotional cues, some patients become more sensitive to positive emotional stimuli. We investigated whether dysregulated positive emotions in bvFTD undermine empathy by making it difficult for patients to share (emotional empathy), recognize (cognitive empathy), and respond (real-world empathy) to emotions in others. Fifty-one participants (26 patients with bvFTD and 25 healthy controls) viewed photographs of neutral, positive, negative, and self-conscious emotional faces and then identified the emotions displayed in the photographs. We used facial electromyography to measure automatic, sub-visible activity in two facial muscles during the task: zygomaticus major (ZM), which is active during positive emotional reactions (i.e., smiling), and corrugator supercilii (CS), which is active during negative emotional reactions (i.e., frowning). Participants rated their baseline positive and negative emotional experience before the task, and informants rated participants’ real-world empathic behavior on the Interpersonal Reactivity Index. The majority of participants also underwent structural magnetic resonance imaging. A mixed effects model found a significant diagnosis X trial interaction: patients with bvFTD showed greater ZM reactivity to neutral, negative (disgust and surprise), self-conscious (proud), and positive (happy) faces than healthy controls. There was no main effect of diagnosis or diagnosis X trial interaction on CS reactivity. Compared to healthy controls, patients with bvFTD had impaired emotion recognition. Multiple regression analyses revealed that greater ZM reactivity predicted worse negative emotion recognition and worse real-world empathy impairment. At baseline, positive emotional experience was higher in bvFTD than healthy controls and also predicted worse negative emotion recognition. Voxel-based morphometry analyses found that smaller volume in the thalamus, midcingulate cortex, posterior insula, anterior temporal pole, amygdala, and inferior frontal gyrus—structures that support emotion generation, interoception, and emotion regulation—was associated with greater ZM reactivity in bvFTD. These findings suggest that dysregulated positive emotional reactivity may relate to reduced empathy in bvFTD by making patients less likely to tune their reactions to the social context and to share, recognize, and respond to others’ feelings and needs.□